La formación profesional docente y su incidencia en el proceso de enseñanza - aprendizaje del área de matemática en los niños y niñas de tercero, cuarto, quinto, sexto y séptimo grados de los subniveles elemental y medio de la escuela de educación básica José Rafael Arízaga Vega, del barrio Zalapa Alto, parroquia El Valle, de la ciudad de Loja. Año Lectivo 2012 – 2013 - Jimenez Azuero, Darwin Segundo (2014)
This thesis is a report on the professional training of teachers and the upcoming results, of understanding by students of elementary and middle levels on third, fourth, fifth, sixth and seventh grades on the understanding of mathematics on basic education at the José Rafael Arízaga Vega school in Zalapa Alto, in the parish El Valle, in Loja on the 2012-2013 school year. To beguin with we must consider the pedagogical training and studies of teachers which should be sound and secure from the start of University where instructors would referred to as examples to follow, thus the student – teachers would be well prepared. On the other hand it is very important that in order to teach mathematics in basic education one should look for the best methods use the most suitable pedagogical means and understand stances of cognitive structures of children. The following methods were used on this research, scientific, descriptive, analytical-synthetic, deductive-theorical. The procedures used were: Interview with the principal of the school. Inquiries with teachers and students of elementary and middle levels of basic education aforesaid. On each sequences according to a preset schedule the activities were followed and let us come up with a systematic analysis of results. This work was mainly directed to find the real level of professional background and efficiency to teachers in the process of teaching learning and understanding of mathematics. It was also guided to find the causes for the lack of professional efficiency and also the present day procedures used by teachers at this school. Finally we reached some conclusions and suggested changes, based on the analysis of obtained data as compared with theorical and conceptual referents. Among the most important were that teachers do not use the right technology to reach the pupil and crate a critical response and interest in the matter. Advice was then given to mark as upmost importance the change of methods to maximize results.